Efficacy and safety of the target puncture technique for treatment of osteoporotic vertebral compression fractures with intravertebral clefts. (9th November 2016) - Yu, Weibo; Liang, De; Jiang, Xiaobing; Yao, Zhensong; Qiu, Ting; Ye, Linqiang
Abstract : Objective: To compare the efficacy and safety of our target puncture technique with the traditional technique during percutaneous kyphoplasty (PKP) for osteoporotic vertebral compression fractures (OVCFs) with intravertebral clefts (IVCs). Methods: 104 patients treated with PKP for single OVCFs with IVCs were retrospectively reviewed. All patients were divided into three groups: cleft filling by the traditional technique (Group A, n=18); interdigitated filling (Group B, n=50); and overfilling by the target technique (Group C, n=36). Oswestry disability index (ODI) and visual analog scale (VAS) scores and radiological evidence of vertebral body height and kyphotic angle, cement leakage, and adjacent vertebral fractures were studied before and after surgery (immediate, 1 and 2 years). Results: The ODI and VAS scores decreased for all patients and no significant difference was found between the three groups after treatment. However, 1 and 2 years after surgery a greater increase in ODI and VAS scores was observed in Group A compared with the other two groups. The initial correction of vertebral body height and kyphotic angle was not significant among the three groups. However, loss of correction was greater in Group A. No significant difference was found in cement leakage. The incidence of adjacent vertebral fractures in Group C was higher than in the other two groups. Conclusions: Different puncture techniques were initially effective for all patients with IVCs. However, cement cleft filling by the traditional technique was found to have less stability causing higher VAS/ODI scores and greater loss of correction. Hence, our target puncture technique was recommended in this study.